Development of a Malabsorption Diagnostics System Based on Mathematical Modeling - Lapta, Stanislav S.; Lapta, Sergey; Solovyova, Olga I. (Internation Science Group, 2020)
Lapta S. Development of a Malabsorption Diagnostics System Based on Mathematical Modeling [Electronic resource] / Lapta Stanislav, Lapta Sergey, Solovyova Olga // Theoretical Outlations for the Implementation and Adaptation of Scientific Achievements in Practice : Abstracts of 22th intern. sci and practical conf., (Helsinki, 22 – 23 june, 2020). – Electronic text data. – Finland, 2020. – P. 52-55. – URL: http://isg-konf.com, free (date of application 29.09.2023).
Keywords: evidence-based medicine; diagnostics of diseases; diagnostic devices; computer modelling